Cognitive functional therapy for disabling nonspecific chronic low back pain: Multiple case-cohort study - O'Sullivan, K.; Dankaerts, W.; O'Sullivan, L.; O'Sullivan, Peter (2015)
Background. Multiple dimensions across the biopsychosocial spectrum are relevant in the management of nonspecific chronic low back pain (NSCLBP). Cognitive functional therapy is a behaviorally targeted intervention that combines normalization of movement and abolition of pain behaviors with cognitive reconceptualization of the NSCLBP problem while targeting psychosocial and lifestyle barriers to recovery. Objective. The purpose of this study was to examine the effectiveness of cognitive functional therapy for people with disabling NSCLBP who were awaiting an appointment with a specialist medical consultant. Design. A multiple case-cohort study (n_26) consisting of 3 phases (A1–B–A2) was conducted. Methods. Measurement phase A1 was a baseline phase during which measurements of pain and functional disability were collected on 3 occasions over 3 months for all participants. During phase B, participants entered a cognitive functional therapy intervention program involving approximately 8 treatments over an average of 12 weeks. Finally, phase A2 was a 12-month, no-treatment follow-up period. Outcomes were analyzed using repeated-measures analysis of variance or Friedman test (with post hoc Bonferroni correction) across 7 time intervals, depending on normality of data distribution. Results. Statistically significant reductions in both functional disability and pain were observed immediately postintervention and were maintained over the 12-month follow-up period. These reductions reached clinical significance for both disability and pain. Secondary psychosocial outcomes, including depression, anxiety, back beliefs, fear of physical activity, catastrophizing, and self-efficacy, were significantly improved after the intervention. Limitations. The study was not a randomized controlled trial. Although primary outcome data were self-reported, the assessor was not blinded. Conclusions. These promising results suggest that cognitive functional therapy should be compared with other conservative interventions for the management of disabling NSCLBP in secondary care settings in large randomized clinical trials.